BMP signaling downstream of the Highwire E3 ligase sensitizes nociceptors. - Ken Honjo; W Daniel Tracey (PLoS Genetics, 2018)
A comprehensive understanding of the molecular machinery important for nociception is essential to improving the treatment of pain. Here, we show that the BMP signaling pathway regulates nociception downstream of the E3 ubiquitin ligase highwire (hiw). hiw loss of function in nociceptors caused antagonistic and pleiotropic phenotypes with simultaneous insensitivity to noxious heat but sensitized responses to optogenetic activation of nociceptors. Thus, hiw functions to both positively and negatively regulate nociceptors. We find that a sensory reception-independent sensitization pathway was associated with BMP signaling. BMP signaling in nociceptors was up-regulated in hiw mutants, and nociceptor-specific expression of hiw rescued all nociception phenotypes including the increased BMP signaling. Blocking the transcriptional output of the BMP pathway with dominant negative Mad suppressed nociceptive hypersensitivity that was induced by interfering with hiw. The up-regulated BMP signaling phenotype in hiw genetic mutants could not be suppressed by mutation in wallenda suggesting that hiw regulates BMP in nociceptors via a wallenda independent pathway. In a newly established Ca2+ imaging preparation, we observed that up-regulated BMP signaling caused a significantly enhanced Ca2+ signal in the axon terminals of nociceptors that were stimulated by noxious heat. This response likely accounts for the nociceptive hypersensitivity induced by elevated BMP signaling in nociceptors. Finally, we showed that 24-hour activation of BMP signaling in nociceptors was sufficient to sensitize nociceptive responses to optogenetically-triggered nociceptor activation without altering nociceptor morphology. Overall, this study demonstrates the previously unrevealed roles of the Hiw-BMP pathway in the regulation of nociception and provides the first direct evidence that up-regulated BMP signaling physiologically sensitizes responses of nociceptors and nociception behaviors.